2021
DOI: 10.2147/jpr.s321119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroacupuncture on Alleviating Prostatodynia and Inflammation in Rats with Chronic Nonbacterial Prostatitis

Abstract: Purpose: Chronic prostatitis (CP) is a common urinary disease characterized by a complex sequence of symptoms including prostatodynia, which results in significant physical pain and mental burden to affected patients. Currently, CP has no standard treatment. Thus, physical therapy electroacupuncture (EA) which has been successful in treating several inflammationrelated pain conditions was used to determine its effect on rats with CP. Materials and Methods: Rats were castrated and treated with beta-estradiol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…As an important part of TCM, acupuncture has been extensively studied in CP/CPPS. Some studies had observed the potential efficacy of acupuncture for CP/CPPS in animal models [78,79] . And some studies have validated the efficacy of acupuncture for CP/CPPS in clinical trials [77,80] .…”
Section: Discussionmentioning
confidence: 99%
“…As an important part of TCM, acupuncture has been extensively studied in CP/CPPS. Some studies had observed the potential efficacy of acupuncture for CP/CPPS in animal models [78,79] . And some studies have validated the efficacy of acupuncture for CP/CPPS in clinical trials [77,80] .…”
Section: Discussionmentioning
confidence: 99%
“…This observation indicated that astrocytes contribute to the development of pain in the later period. Therefore, astrocytes play an important part in the resistant pain of chronic abacterial prostatitis [ 67 68 ]. Various evidence shows the activation and sensitization of spinal cords in chronic prostatitis.…”
Section: Autonomic Nervous System Dysfunction’s Close Relation With C...mentioning
confidence: 99%
“…Pain. Astrocytes have been proven to be involved in EAP-induced pain and potential targets for certain interventions in the past decade or so [99][100][101][102]. Zhang et al found increasing activated astrocytes in the L6-S1 spinal dorsal horn of EAP rats where substance P (SP) was also elevated indicating a possible association [99].…”
Section: Astrocytesmentioning
confidence: 99%
“…Also, SP, NK-1R, TNF-α, and iNOS were elevated in the L5-S2 spinal dorsal horn [100]. It was reported that electroacupuncture could release pain symptoms of chronic prostatitis rats while inhibiting astrocyte activation and CXCL1 expressions in astrocytes in the L5-S2 spinal dorsal horn, indicating that CXCL1 in astrocytes might be a potential target for chronic prostatitis [101]. Additionally, Liu et al detected elevated CCL2 expression of the lower dorsal horn of the spinal cord which was mainly from GFAP-positive astrocytes and NeuNpositive aferent neurons [103].…”
Section: Astrocytesmentioning
confidence: 99%